Disorientation in the unmaking of high‐rise homes. Issue 2 (27th January 2021) - Dorignon, Louise; Nethercote, Megan
Abstract : This paper expands our understanding of vertical urbanism, and specifically the experience of home in high‐rise housing, by assessing and mobilising a "disorientated geographies" approach. It follows Bissell and Gorman‐Murray's recent call for researchers to better account for the logics of disconnection and undoing in geographical inquiry. Building on their exploration of "disorientated geographies, " this paper examines the lived experience of three single men living in high‐rise housing to revisit the high‐rise as home. It aims to advance prevailing understandings of urban vertical living and more specifically of the processes through which these homes are made and unmade. Drawing on in‐depth interviews with apartment dwellers in new high‐rise housing in London and Melbourne, we explore residents' loss of orienting relations through their feelings of frustration, restlessness, and disappointment. We consider how these emotional states contribute to destabilise their homes as these three men struggle to comprehend and orient themselves within the socio‐spatial environment of the high‐rise, and specifically an environment compromised by design and build quality issues. We argue that disorientation provides a useful but undervalued vantage point from which to understand the making and unmaking of vertical homes. In so doing, we foreground and sharpen understandings of the role of verticality, in particular, in these processes of home‐unmaking. The contribution of the paper is two‐fold. Conceptually, it both expands the application of disorientated geographies into a novel urban setting and broadens its frames of reference by examining other bodily experiences and emotions. Empirically, we advance understandings of the lived experience of vertical urbanisms by drawing new and productive links between verticality and disorientation that move us beyond consideration of purely physiological responses, such as vertigo or dizziness, to high‐rise living, to better account for a fuller range of bodily, emotional, and social practices. Abstract : This paper expands our understanding of vertical urbanism, and specifically the experience of home in high‐rise housing by assessing and mobilising a "disorientated geographies" approach. It follows Bissell and Gorman‐Murray's recent call for researchers to better account for the logics of disconnection and undoing in geographical inquiry. Building on their exploration of "disorientated geographies, " this paper examines the lived experience of three single men living in high‐rise housing to revisit the high‐rise as home.